The Effectiveness of the Implementation of the Urban Farming Program in Indonesia - Metin c; Didik G. Suharto; Rina Herlina Haryanti (Journal Of Social Science (JoSS), 2023)
Urban agriculture in the current era is considered very important to meet the food needs of urban people in various countries. This study aims to determine how effective urban agricultural activities are and to what extent urban agriculture can provide benefits by realizing government policy or program objectives. This research is qualitative research that uses a library research approach. The results show that the indicators of Program Target Accuracy, Program Socialization, Program Objectives, and Program Monitoring show that urban farming programs in all major cities in Indonesia are working well and have resulted in many better communities.